Self-regeneration high thermal conductivity and moisture absorption composite gel for flexible device thermal management and preparation method and application thereof
Patent Information
- Application Number
- CN202610797848.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-06-04
AI Technical Summary
[0009]为了克服现有技术中普通凝胶导热能力不足、吸湿盐易流失、补水依赖外部供液及循环稳定性差等问题,本发明提出了一种用于柔性器件热管理的自再生高导热吸湿复合凝胶及其制备方法与应用,本发明通过连续导热增强网络和稳定化吸湿组分协同构筑的复合凝胶,使器件热量能够快速传入凝胶内部并向蒸发表面转移,同时利用吸湿盐在环境湿度作用下实现自主吸水补水,从而在无需独立供液装置的条件下实现循环热管理
[0047]1.兼具快速导热与蒸发散热能力
Smart Images

Figure CN122325665B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flexible thermal management materials and devices, and particularly relates to a self-regenerating high thermal conductivity and moisture-absorbing composite gel for thermal management of flexible devices, its preparation method and application. Background Technology
[0002] With the rapid development of flexible electronics, wearable devices, flexible sensors, flexible thermoelectric devices, and miniaturized energy storage devices, the problem of heat accumulation under bending, skin contact, localized high power density, and confined space conditions is becoming increasingly prominent. Compared with traditional rigid heat sinks, air-cooled systems, or liquid-cooled systems, thermal management of flexible devices places greater emphasis on the flexibility, adhesion, lightweight, and passive operation capabilities of materials.
[0003] Hydrogels have attracted widespread attention in the field of passive heat dissipation in recent years due to their high water content, softness, adhesion, and ability to remove a large amount of latent heat through water evaporation. However, existing hydrogel thermal management systems generally have the following shortcomings.
[0004] First, ordinary polymer gels have low intrinsic thermal conductivity, making it difficult for the heat generated by the device to be transferred from the heat source interface to the gel in a timely manner. This results in the gel's evaporative heat dissipation potential not being fully utilized, especially in scenarios with high heat flux density or transient heating, where heat tends to accumulate at the interface.
[0005] Second, existing hygroscopic evaporative gels mostly focus on water retention or moisture absorption functions, often using simple salt impregnation to improve moisture absorption capacity. However, salt is prone to migration, precipitation, or leakage, affecting cycle stability, device compatibility, and service life.
[0006] Third, many evaporative heat dissipation gels rely on external liquid replenishment or periodic artificial water replenishment, which is difficult to meet the continuous thermal management needs of actual flexible devices under closed, portable or long-term operating conditions.
[0007] Fourth, in existing technologies, thermal conductivity enhancement, moisture absorption and water replenishment, thermal buffering and evaporative heat dissipation are usually dispersed in different structures or independent modules, lacking an integrated material system that takes into account flexible adhesion, rapid thermal conduction, environmental water replenishment and regeneration, and stable operation in cycles.
[0008] Therefore, developing a high thermal conductivity and moisture-absorbing composite gel that can rapidly transfer heat, maintain flexibility and moisture absorption capabilities, and achieve self-regeneration in the environment is of great significance for improving the passive thermal management performance of flexible devices. Summary of the Invention
[0009] To overcome the problems of insufficient thermal conductivity, easy loss of hygroscopic salt, reliance on external liquid supply for water replenishment, and poor cycle stability in existing technologies, this invention proposes a self-regenerating high thermal conductivity and hygroscopic composite gel for thermal management of flexible devices, as well as its preparation method and application. This invention constructs a composite gel through the synergistic construction of a continuous thermal conductivity enhancement network and a stabilized hygroscopic component, enabling the device's heat to be rapidly transferred into the gel and towards the evaporation surface. At the same time, the hygroscopic salt achieves autonomous water absorption and replenishment under the influence of ambient humidity, thereby achieving cyclic thermal management without the need for an independent liquid supply device.
[0010] To achieve the above objectives, the present invention provides the following technical solution:
[0011] This invention provides a self-regenerating, highly thermally conductive, and moisture-absorbing composite gel for thermal management of flexible devices, wherein the composite gel is a single-layer integral structure or a multi-layer composite structure;
[0012] The self-regenerating high thermal conductivity and moisture-absorbing composite gel comprises a flexible polymer gel matrix, a through-type thermal conductivity enhancement structure, and a stabilized moisture-absorbing component.
[0013] The flexible polymer gel matrix is formed by cross-linking polymerization of acrylamide monomers;
[0014] The through-type thermally conductive reinforcement structure is formed by continuously arranging highly thermally conductive fillers along the thickness direction and / or planar direction inside the gel matrix;
[0015] The stabilized hygroscopic component comprises hygroscopic salts, which are immobilized in the gel matrix by physical confinement, chemical association, or carrier encapsulation.
[0016] Technical principle: The self-regenerating high thermal conductivity and moisture-absorbing composite gel of the present invention achieves continuous thermal management of flexible devices through the following synergistic methods: the through-type thermal conductivity enhancement network rapidly transfers the heat generated by the flexible device to the inside of the gel and / or the gel evaporation surface; the stabilized moisture-absorbing component actively adsorbs moisture under the action of ambient humidity to replenish the moisture lost by the gel during evaporation and heat dissipation, thereby enabling the composite gel to achieve self-regenerating cycle thermal management without relying on an external water replenishment device.
[0017] Furthermore, the acrylamide monomer is selected from one or at least two of acrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide, and methacrylamide. Preferably, acrylamide is specifically selected as the acrylamide monomer.
[0018] Furthermore, the flexible polymer gel matrix also contains a comonomer selected from one or at least two of acrylic acid, methacrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, N-vinylpyrrolidone, and hydroxyethyl acrylate. Preferably, acrylic acid is selected as the comonomer.
[0019] Furthermore, the crosslinking agent used for crosslinking polymerization is selected from one or at least two of N,N'-methylenebisacrylamide (MBAA), polyethylene glycol diacrylate, ionic crosslinking agents, and hydrogen bonding agents. Preferably, MBAA is selected as the crosslinking agent.
[0020] Furthermore, the through-type thermally conductive enhancement structure is formed by arranging sheet-like, fibrous, or network-like high thermal conductivity materials through external field-induced orientation, template-confined assembly, or casting and shearing to create a continuous heat transfer path. The high thermal conductivity material is selected from one or at least two of hexagonal boron nitride, alumina, aluminum nitride, graphene, carbon nanotubes, graphite sheets, carbon fibers, and metal nanowires. Preferably, sheet-like hexagonal boron nitride is selected and preferentially arranged along the planar direction through casting and shearing to form a continuous heat transfer path.
[0021] Furthermore, the stabilized hygroscopic component is immobilized through at least one of the following methods: forming ion associations with carboxyl, sulfonic acid, or hydroxyl groups in the gel matrix; loading it into porous microparticles or microcapsules and then embedding it into the gel; or exhibiting a concentration gradient distribution along the gel thickness direction; the hygroscopic salt is selected from one or at least two of lithium chloride, calcium chloride, magnesium chloride, lithium bromide, potassium acetate, and potassium formate. Preferably, the carboxyl groups introduced by acrylic acid are used to form ion associations with lithium chloride for immobilization, or lithium chloride is pre-loaded onto porous cellulose particles and then embedded into the gel.
[0022] Furthermore, the initiator is ammonium persulfate (APS).
[0023] Furthermore, in the single-layer integrated structure, the flexible polymer gel matrix, the through-type thermally conductive enhancement structure, and the stabilizing moisture-absorbing component are uniformly composited within the same layer. Preferably, acrylamide, acrylic acid, crosslinking agent, modified hexagonal boron nitride, and lithium chloride are mixed in the same precursor solution and polymerized in one step to obtain the single-layer composite gel.
[0024] Furthermore, in the multilayer composite structure, each layer comprises a flexible polymer gel matrix, and the multilayer composite structure includes at least a thermally conductive layer and a moisture-absorbing evaporation layer. The thermally conductive layer comprises a through-type thermally conductive enhancement structure, and the moisture-absorbing evaporation layer comprises a stabilizing moisture-absorbing component. Preferably, the thermally conductive layer contains 8g of hexagonal boron nitride, and the moisture-absorbing evaporation layer contains lithium chloride loaded in porous cellulose particles. The content of thermally conductive filler and moisture-absorbing salt both exhibit interlayer differences.
[0025] Furthermore, the multilayer composite structure also includes a heat storage buffer layer located between the thermally conductive layer and the moisture-absorbing evaporation layer. Preferably, a heat storage buffer layer with a thickness of 0.4 mm is provided between the thermally conductive layer and the moisture-absorbing evaporation layer. This layer does not contain moisture-absorbing salts or thermally conductive fillers and is used to smooth heat flow fluctuations.
[0026] Furthermore, the through-type thermally conductive enhanced structure is formed in any of the following ways: high thermal conductivity material is freeze-cast to form directional channels and then filled; layer-by-layer stacking assembly; or after surface modification, it undergoes covalent bonding, hydrogen bonding, electrostatic association, or coordination with the polymer skeleton to reduce interfacial thermal resistance. Preferably, a silane coupling agent is used to surface modify the high thermal conductivity material hexagonal boron nitride, enabling it to form a covalent bond with the polymer skeleton and reduce interfacial thermal resistance.
[0027] Furthermore, the stabilized hygroscopic component is introduced into the gel framework in any of the following ways: the hygroscopic salt is pre-loaded onto a porous carrier, microcapsule, or layered material before embedding; the hygroscopic salt forms a concentration gradient distribution along the gel thickness to achieve functional zones for moisture absorption, hydration, and evaporative heat dissipation; or it is fixed by confined impregnation after polymerization and surface coating with a salt-barrier layer. Preferably, the method of pre-loading the hygroscopic salt onto a porous carrier before embedding, or the microcapsule encapsulation method, is used to encapsulate lithium chloride in polyurea microcapsules and then disperse it in the gel.
[0028] Furthermore, the outer surface of the composite gel is provided with a surface radiation regulation layer, which has a medium-to-high infrared emissivity and is used to enhance heat dissipation in conjunction with evaporative cooling. Preferably, a thin layer with high infrared emissivity and a thickness of 20~100μm is coated on the outer surface of the hygroscopic evaporation layer.
[0029] This invention also provides a method for preparing the above-mentioned self-regenerating high thermal conductivity and moisture-absorbing composite gel, wherein when the self-regenerating high thermal conductivity and moisture-absorbing composite gel is a single-layer integral structure, the method includes the following steps:
[0030] Prepare a precursor solution containing acrylamide monomers, crosslinking agents, and initiators;
[0031] High thermal conductivity filler is dispersed in the precursor liquid, and a through-type thermally enhanced structure is constructed by directional arrangement or template confinement.
[0032] Hygroscopic salts are introduced into the precursor solution in an immobilized manner;
[0033] The polymerization reaction is initiated to solidify the precursor liquid into a gel in one step, resulting in a single-layer monolithic self-regenerating high thermal conductivity and moisture-absorbing composite gel.
[0034] When the composite gel has a multilayer composite structure, it is prepared by stepwise casting or layer-by-layer polymerization, including the following steps:
[0035] Precursor solutions for the thermally conductive layer, the thermal storage buffer layer, and the hygroscopic evaporation layer were prepared separately. The thermally conductive layer precursor solution contained a higher content of high thermal conductivity filler than the hygroscopic evaporation layer precursor solution, and the hygroscopic evaporation layer precursor solution contained a higher content of hygroscopic salts than the thermally conductive layer precursor solution.
[0036] The heat-conducting layer precursor liquid is cast into shape and prepolymerized or partially polymerized to form a heat-conducting layer.
[0037] A heat storage buffer layer precursor liquid is poured onto the thermally conductive layer, and a second polymerization step is carried out to form a heat storage buffer layer.
[0038] A moisture-absorbing evaporation layer precursor liquid is poured onto the heat storage buffer layer and then polymerized to form a moisture-absorbing evaporation layer, resulting in a multi-layered composite structure of a self-regenerating high thermal conductivity and moisture-absorbing composite gel.
[0039] Furthermore, when the self-regenerating high thermal conductivity and hygroscopic composite gel is a single-layer integral structure, the amount of each component in the precursor liquid by weight is as follows: 10 parts by weight of acrylamide monomer, 1.5 parts by weight of comonomer, 0.08 parts by weight of crosslinking agent, 0.10 parts by weight of initiator, 3-9 parts by weight of high thermal conductivity filler, and 4-12 parts by weight of hygroscopic salt.
[0040] Furthermore, when the self-regenerating high thermal conductivity and moisture-absorbing composite gel has a multilayer composite structure, the amounts of each component in the thermally conductive layer precursor solution, by weight, are: 8-10 parts by weight of acrylamide monomers, 0.5-2 parts by weight of comonomers, 0.04-0.10 parts by weight of crosslinking agent, 0.05-0.12 parts by weight of initiator, 6-10 parts by weight of high thermal conductivity filler, and 60-100 parts by weight of water; the amounts of each component in the heat storage buffer layer precursor solution, by weight, are: 8-10 parts by weight of acrylamide monomers, The components in the hygroscopic evaporation layer precursor solution are: 0.5-2 parts by weight of comonomer, 0.04-0.10 parts by weight of crosslinking agent, 0.05-0.12 parts by weight of initiator, and 60-100 parts by weight of water; the amounts of each component in the hygroscopic evaporation layer precursor solution are as follows (by weight): 8-10 parts by weight of acrylamide monomer, 0.5-2 parts by weight of comonomer, 0.04-0.10 parts by weight of crosslinking agent, 0.05-0.12 parts by weight of initiator, 2-8 parts by weight of hygroscopic salt, 2-10 parts by weight of porous carrier, and 60-100 parts by weight of water.
[0041] Furthermore, the preparation method also includes post-treatment of the obtained composite gel, which includes wiping and trimming the surface of the gel after allowing it to stand and equilibrate for 24 hours; or coating the outermost layer with a thin layer of high infrared emissivity.
[0042] Furthermore, the immobilization of the hygroscopic salts is achieved through any of the following methods: pre-polymerization complexation, post-polymerization confined impregnation, microencapsulation, carrier loading followed by embedding, or surface coating with a salt-barrier layer. Preferably, pre-polymerization complexation immobilization (carboxyl-lithium ion association), carrier loading followed by embedding immobilization (lithium chloride loaded onto porous cellulose particles), or microencapsulation immobilization is used.
[0043] The present invention also provides an application of the above-mentioned self-regenerating high thermal conductivity and moisture-absorbing composite gel in the thermal management of flexible electronic devices, wearable devices, flexible thermoelectric devices or skin-attached sensors.
[0044] Furthermore, the thermal management includes at least one of rapid heat transfer, peak heat buffering, evaporative cooling, environmental water replenishment and regeneration, and recycling. Preferably, the composite gel is attached to the hot end of the flexible thermoelectric device to achieve rapid heat transfer, evaporative cooling, and environmental water replenishment and regeneration during shutdown.
[0045] Furthermore, the self-regenerating high thermal conductivity and moisture-absorbing composite gel is used in the form of a thermal management component. The thermal management component includes a heat source adhesion interface layer and the composite gel. The composite gel is disposed on at least one side of the heat source adhesion interface layer for heat conduction, heat storage, and evaporative heat dissipation of the flexible device. Preferably, the composite gel is attached to the hot end surface of the flexible thermoelectric device via an interface adhesion layer to form the thermal management component.
[0046] Compared with the prior art, the present invention has the following advantages and technical effects:
[0047] 1. It combines rapid heat conduction and evaporative heat dissipation capabilities.
[0048] This invention constructs a continuous thermally enhanced network inside the gel, enabling heat to be rapidly transferred into the gel interior and evaporation surface instead of being confined to the vicinity of the heat source interface. This significantly improves the gel's efficiency in utilizing device heat and its heat dissipation response speed.
[0049] 2. Possesses self-water replenishment and recycling capabilities.
[0050] This invention, through the design of a stabilized hygroscopic component, enables the gel to absorb moisture from the environment during non-working phases, replenishing the water lost through evaporation. This achieves self-regenerating circulating thermal management without the need for an external independent liquid supply device, making it more suitable for long-term use scenarios of flexible devices.
[0051] 3. It can reduce salt loss and improve circulation stability.
[0052] This invention does not simply impregnate the hygroscopic salt in the gel, but uses confined loading, complexation fixation, microcapsule encapsulation or carrier embedding to improve the stability of the hygroscopic salt in the gel, which helps to suppress leakage, crystallization and performance degradation during use.
[0053] 4. Combines flexible adhesion with thermal cushioning function
[0054] The composite gel of this invention retains the flexibility, bendability, and interfacial adaptability of the polymer gel itself, enabling it to effectively adhere to curved or irregular heat source surfaces. Simultaneously, the gel's inherent aqueous structure provides a certain thermal buffering effect, which can weaken peak thermal shocks and improve the thermal stability of the device.
[0055] 5. It has strong structural designability and application adaptability.
[0056] This invention can be designed as a single-layer composite gel, or as a layered structure consisting of a thermally conductive layer, a thermally stored buffer layer, and a moisture-absorbing evaporation layer. It can also be combined with a radiative heat dissipation layer, an interfacial adhesion layer, etc., which facilitates optimization according to the heat flux density, bending conditions, and ambient humidity of different flexible devices. Attached Figure Description
[0057] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0058] Figure 1 The graph shows the heat dissipation performance of the composite gels obtained in Examples 1, 2, 3, and 6 and Comparative Examples 1 and 2.
[0059] Figure 2 The graph shows the cyclic stability of the composite gels obtained in Examples 1, 4, 5, 7, 8 and Comparative Example 3. Detailed Implementation
[0060] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0061] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0062] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0063] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This specification and embodiments are merely exemplary.
[0064] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0065] This invention provides a self-regenerating, highly thermally conductive, and moisture-absorbing composite gel for thermal management of flexible devices. The composite gel is a single-layer integral structure or a multi-layer composite structure.
[0066] The self-regenerating high thermal conductivity and moisture-absorbing composite gel comprises a flexible polymer gel matrix, a through-type thermal conductivity enhancement structure, and a stabilized moisture-absorbing component.
[0067] The flexible polymer gel matrix is formed by cross-linking polymerization of acrylamide monomers;
[0068] The through-type thermally conductive reinforcement structure is formed by continuously arranging highly thermally conductive fillers in the gel matrix along the thickness direction and / or the planar direction;
[0069] The stabilized hygroscopic component contains hygroscopic salts, which are immobilized in the gel matrix through physical confinement, chemical association, or carrier encapsulation.
[0070] In some preferred embodiments of the present invention, the acrylamide monomer is selected from one or at least two of acrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide, and methacrylamide. For example, acrylamide is specifically selected as the acrylamide monomer.
[0071] In some preferred embodiments of the present invention, the flexible polymer gel matrix further comprises a comonomer selected from one or at least two of acrylic acid, methacrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, N-vinylpyrrolidone, and hydroxyethyl acrylate. For example, acrylic acid is specifically selected as the comonomer.
[0072] In some preferred embodiments of the present invention, the crosslinking agent used for crosslinking polymerization is selected from one or at least two of N,N'-methylenebisacrylamide (MBAA), polyethylene glycol diacrylate, ionic crosslinking agents, and hydrogen bonding agents. For example, MBAA is selected as the crosslinking agent.
[0073] In some preferred embodiments of the present invention, the through-type thermally conductive enhancement structure is formed by arranging sheet-like, fibrous, or network-like high thermal conductivity materials through external field-induced orientation, template-confined assembly, or casting and shearing to form a continuous heat transfer path; the high thermal conductivity material is selected from one or at least two of hexagonal boron nitride, alumina, aluminum nitride, graphene, carbon nanotubes, graphite sheets, carbon fibers, and metal nanowires. For example, sheet-like hexagonal boron nitride is selected and preferentially arranged along the planar direction through casting and shearing to form a continuous heat transfer path.
[0074] In some preferred embodiments of the present invention, the stabilized hygroscopic component is immobilized by at least one of the following methods: forming ion associations with carboxyl, sulfonic acid, or hydroxyl groups in the gel matrix; loading it into porous microparticles or microcapsules and then embedding it into the gel; or exhibiting a concentration gradient distribution along the gel thickness direction; the hygroscopic salt is selected from one or at least two of lithium chloride, calcium chloride, magnesium chloride, lithium bromide, potassium acetate, and potassium formate. Exemplarily, the carboxyl groups introduced by acrylic acid are used to form ion associations with lithium chloride, or lithium chloride is pre-loaded onto porous cellulose particles before embedding it into the gel.
[0075] In some preferred embodiments of the present invention, the initiator is ammonium persulfate (APS).
[0076] In some preferred embodiments of the present invention, in the monolayer integral structure, a flexible polymer gel matrix, a through-type thermally conductive enhancement structure, and a stabilizing moisture-absorbing component are uniformly composited within the same layer. For example, acrylamide, acrylic acid, a crosslinking agent, modified hexagonal boron nitride, and lithium chloride are mixed in the same precursor solution and polymerized in one step to obtain a monolayer composite gel.
[0077] In some preferred embodiments of the present invention, each layer of the multilayer composite structure comprises a flexible polymer gel matrix. The multilayer composite structure includes at least a thermally conductive layer and a moisture-absorbing evaporation layer. The thermally conductive layer comprises a through-type thermally conductive enhancement structure, and the moisture-absorbing evaporation layer comprises a stabilized moisture-absorbing component. For example, the thermally conductive layer contains 8g of hexagonal boron nitride, and the moisture-absorbing evaporation layer contains lithium chloride loaded in porous cellulose particles. The contents of the thermally conductive filler and the moisture-absorbing salt both exhibit interlayer differences.
[0078] In some preferred embodiments of the present invention, the multilayer composite structure further includes a heat storage buffer layer located between the thermally conductive layer and the moisture-absorbing evaporation layer. For example, a heat storage buffer layer with a thickness of 0.4 mm is provided between the thermally conductive layer and the moisture-absorbing evaporation layer. This layer does not contain moisture-absorbing salts or thermally conductive fillers and is used to smooth heat flow fluctuations.
[0079] In some preferred embodiments of the present invention, the through-type thermally enhanced structure is further formed by any of the following methods: high thermal conductivity material is freeze-cast to form directional channels and then filled; layer-by-layer stacking assembly; or surface modification followed by covalent bonding, hydrogen bonding, electrostatic association, or coordination with the polymer skeleton to reduce interfacial thermal resistance. For example, a silane coupling agent is used to surface modify the high thermal conductivity material hexagonal boron nitride, enabling it to form a covalent bond with the polymer skeleton and reduce interfacial thermal resistance.
[0080] In some preferred embodiments of the present invention, the stabilized hygroscopic component is further introduced into the gel framework in any of the following ways: the hygroscopic salt is preloaded onto a porous carrier, microcapsule, or layered material before embedding; the hygroscopic salt forms a concentration gradient distribution along the gel thickness direction to achieve functional zones for moisture absorption, water replenishment, and evaporative heat dissipation; or it is fixed by confined impregnation after polymerization and surface coating with a salt-barrier layer. For example, lithium chloride is encapsulated in polyurea microcapsules and then dispersed in the gel by preloading the hygroscopic salt onto a porous carrier or by microcapsule encapsulation.
[0081] In some preferred embodiments of the present invention, the outer surface of the composite gel is further provided with a surface radiation modulation layer, which has a medium-to-high infrared emissivity and is used to enhance heat dissipation in conjunction with evaporative cooling. For example, a thin layer with high infrared emissivity, with a thickness of 20-100 μm, is coated on the outer surface of the hygroscopic evaporation layer.
[0082] This invention also provides a method for preparing the above-mentioned self-regenerating high thermal conductivity and moisture-absorbing composite gel. When the self-regenerating high thermal conductivity and moisture-absorbing composite gel is a single-layer integral structure, the method includes the following steps:
[0083] Prepare a precursor solution containing acrylamide monomers, crosslinking agents, and initiators;
[0084] High thermal conductivity fillers are dispersed in a precursor solution and a through-type thermally enhanced structure is constructed by directional arrangement or template confinement.
[0085] Hygroscopic salts are introduced into the precursor solution in an immobilized manner;
[0086] The polymerization reaction is initiated to solidify the precursor liquid into a gel in one step, resulting in a single-layer monolithic self-regenerating high thermal conductivity and moisture-absorbing composite gel.
[0087] When the composite gel has a multilayer composite structure, it is prepared by stepwise casting or layer-by-layer polymerization, including the following steps:
[0088] Precursor solutions for the thermally conductive layer, the thermal storage buffer layer, and the hygroscopic evaporation layer were prepared separately. The thermally conductive layer precursor solution contained a higher content of high thermal conductivity filler than the hygroscopic evaporation layer precursor solution, and the hygroscopic evaporation layer precursor solution contained a higher content of hygroscopic salts than the thermally conductive layer precursor solution.
[0089] The heat-conducting layer precursor liquid is cast into shape and prepolymerized or partially polymerized to form a heat-conducting layer.
[0090] A heat storage buffer layer precursor liquid is poured onto the heat-conducting layer, and a second polymerization step is carried out to form a heat storage buffer layer.
[0091] A moisture-absorbing evaporation layer precursor liquid is poured onto the heat storage buffer layer and then polymerized to form a moisture-absorbing evaporation layer, resulting in a multi-layered composite structure of a self-regenerating high thermal conductivity and moisture-absorbing composite gel.
[0092] In some preferred embodiments of the present invention, when the self-regenerating high thermal conductivity and hygroscopic composite gel is a single-layer integral structure, the amount of each component in the precursor liquid by weight is as follows: 10 parts by weight of acrylamide monomer, 1.5 parts by weight of comonomer, 0.08 parts by weight of crosslinking agent, 0.10 parts by weight of initiator, 3-9 parts by weight of high thermal conductivity filler, and 4-12 parts by weight of hygroscopic salt.
[0093] In some preferred embodiments of the present invention, when the self-regenerating high thermal conductivity and moisture-absorbing composite gel has a multilayer composite structure, the amounts of each component in the thermally conductive layer precursor solution, by weight, are: 8-10 parts by weight of acrylamide monomers, 0.5-2 parts by weight of comonomers, 0.04-0.10 parts by weight of crosslinking agent, 0.05-0.12 parts by weight of initiator, 6-10 parts by weight of high thermal conductivity filler, and 60-100 parts by weight of water; the amounts of each component in the heat storage buffer layer precursor solution, by weight, are: 8-10 parts by weight of acrylamide monomers. The components in the hygroscopic evaporation layer precursor solution are: 8-10 parts by weight of acrylamide monomers, 0.5-2 parts by weight of comonomers, 0.04-0.10 parts by weight of crosslinking agent, 0.05-0.12 parts by weight of initiator, and 60-100 parts by weight of water; the amounts of each component in the hygroscopic evaporation layer precursor solution are as follows (by weight): 8-10 parts by weight of acrylamide monomers, 0.5-2 parts by weight of comonomers, 0.04-0.10 parts by weight of crosslinking agent, 0.05-0.12 parts by weight of initiator, 2-8 parts by weight of hygroscopic salts, 2-10 parts by weight of porous carrier, and 60-100 parts by weight of water.
[0094] In some preferred embodiments of the present invention, the preparation method further includes post-treatment of the obtained composite gel, which includes wiping and trimming the surface of the gel after allowing it to stand for equilibration for 24 hours; or coating the outermost layer with a thin layer of high infrared emissivity.
[0095] In some preferred embodiments of the present invention, the immobilization of hygroscopic salts is achieved by any of the following methods: prepolymerization complexation, postpolymerization confined impregnation, microencapsulation, carrier loading followed by embedding, or surface coating with a salt-barrier layer. For example, prepolymerization complexation immobilization (carboxyl-lithium ion association), carrier loading followed by embedding immobilization (lithium chloride loaded onto porous cellulose particles), or microencapsulation immobilization are employed.
[0096] The present invention also provides an application of the above-mentioned self-regenerating high thermal conductivity and moisture-absorbing composite gel in the thermal management of flexible electronic devices, wearable devices, flexible thermoelectric devices or skin-attached sensors.
[0097] In some preferred embodiments of the present invention, thermal management includes at least one of rapid heat transfer, peak heat buffering, evaporative cooling, environmental water replenishment and regeneration, and recycling. For example, a composite gel is attached to the hot end of a flexible thermoelectric device to achieve rapid heat transfer, evaporative cooling, and environmental water replenishment and regeneration during shutdown.
[0098] In some preferred embodiments of the present invention, the self-regenerating high thermal conductivity and moisture-absorbing composite gel is used in the form of a thermal management component. The thermal management component includes a heat source adhesion interface layer and a composite gel. The composite gel is disposed on at least one side of the heat source adhesion interface layer for conducting, storing, and dissipating heat through evaporation in the flexible device. For example, the composite gel is attached to the hot end surface of the flexible thermoelectric device via an interface adhesion layer to form the thermal management component.
[0099] In the embodiments of this invention, unless otherwise specified, "parts" refers to "number of parts by weight".
[0100] The specific preparation method of silane coupling agent modified hexagonal boron nitride in this embodiment of the invention is as follows: 10 g of hexagonal boron nitride is added to 200 mL of ethanol / water mixed solution, wherein the volume ratio of ethanol to water is 9:1, and ultrasonically dispersed for 30 min; then 0.5 g of silane coupling agent KH-550 is added, the pH of the system is adjusted to 4-5, and the reaction is stirred at 60 ℃ for 4 h; after the reaction is completed, the mixture is centrifuged, repeatedly washed with ethanol and deionized water, and vacuum dried at 60 ℃ for 12 h to obtain silane coupling agent modified hexagonal boron nitride. Hexagonal boron nitride is surface modified with a silane coupling agent to improve its dispersibility in the gel precursor solution and enhance its interfacial bonding with the polymer gel backbone.
[0101] The technical solution of the present invention will be further illustrated by the following embodiments.
[0102] Example 1: Single-layer self-regenerating high thermal conductivity and moisture-absorbing composite gel
[0103] 1) Preparation of gel precursor solution
[0104] Add 10g acrylamide and 1.5g acrylic acid to 88g deionized water, stir to dissolve, then add 0.08g MBAA as a crosslinking agent and 0.10g APS as an initiator to obtain the precursor solution.
[0105] 2) Construction of a through-type thermally enhanced structure
[0106] 6g of hexagonal boron nitride (h-BN) powder modified with silane coupling agent was added to the prepared precursor liquid. The mixture was mechanically stirred and ultrasonically dispersed for 30min in sequence. Then, the sheet-like hexagonal boron nitride was preferentially arranged along the planar direction by casting shearing and formed a locally through thermally conductive structure to obtain the precursor system.
[0107] 3) Introduction of stabilizing moisture-absorbing components
[0108] Dissolve 8g of lithium chloride in 20mL of water and add it to the precursor system. Utilize the carboxyl groups introduced by acrylic acid to form ion association with lithium chloride to improve the fixation degree of the hygroscopic salt in the gel, thus obtaining a mixed precursor solution.
[0109] 4) Polymerization into a gel
[0110] The above-mentioned mixed precursor liquid was injected into a mold and polymerized at 60°C for 3 hours to obtain a flexible composite gel sheet.
[0111] 5) Post-processing
[0112] The obtained flexible composite gel sheet was left to stand for equilibration for 24 hours, and the surface was wiped and the edges were trimmed to obtain a single-layer self-regenerating high thermal conductivity and moisture-absorbing composite gel with a thickness of 1 mm.
[0113] Example 2
[0114] Same as Example 1, except that the amount of hexagonal boron nitride (h-BN) powder modified with silane coupling agent is changed to 3g.
[0115] Example 3
[0116] Same as Example 1, except that the amount of hexagonal boron nitride (h-BN) powder modified with silane coupling agent is changed to 9g.
[0117] Example 4
[0118] Same as Example 1, except that 4g of lithium chloride was dissolved in 20mL of water and then added to the precursor system.
[0119] Example 5
[0120] Same as Example 1, except that 12g of lithium chloride was dissolved in 20mL of water and then added to the precursor system.
[0121] Example 6: Multilayer synergistic self-regenerating high thermal conductivity and moisture-absorbing composite gel
[0122] 1) Preparation of thermal conductive layer
[0123] Mix 8g acrylamide, 1.0g acrylic acid and 80g deionized water, add 0.06g MBAA and 0.08g APS, then add 6g hexagonal boron nitride, stir and shear to form a thermally conductive layer precursor liquid, cast and prepolymerize to form a thermally conductive layer with a thickness of 0.4 mm.
[0124] 2) Preparation of thermal storage buffer layer
[0125] 8 g of acrylamide and 1.0 g of acrylic acid were added to 75 g of deionized water and stirred to dissolve. Then, 0.06 g of MBAA and 0.08 g of APS were added to obtain a heat storage buffer layer precursor liquid that does not contain hygroscopic salts and high thermal conductivity fillers. The precursor liquid was cast onto the thermally conductive layer and subjected to a second polymerization step to form a heat storage buffer layer with a thickness of 0.4 mm.
[0126] 3) Preparation of the moisture-absorbing evaporation layer
[0127] Mix 8 g acrylamide, 1.0 g acrylic acid and 80 g deionized water, add 0.06 g N,N'-methylenebisacrylamide, 0.08 g ammonium persulfate and 8 g lithium chloride, stir evenly and then cast onto the surface of the heat storage buffer layer to complete the final polymerization, forming a moisture-absorbing evaporation layer with a thickness of 0.4 mm.
[0128] 4) Surface functionalization
[0129] 0.5 g of polyvinylidene fluoride and 1.5 g of silica particles were added to 20 mL of N,N-dimethylformamide and stirred at 60 °C until the polyvinylidene fluoride was fully dissolved and the silica particles were uniformly dispersed to obtain a high infrared emissivity coating solution. The coating solution was uniformly coated on the outer surface of the moisture-absorbing evaporation layer and dried to form a 50 μm thick high infrared emissivity thin layer, thus obtaining a multilayer synergistic self-regenerating high thermal conductivity and moisture-absorbing composite gel.
[0130] Example 7
[0131] Similar to Example 6, except that lithium chloride is replaced with lithium chloride supported on porous cellulose particles. The specific steps are as follows: 8 g of lithium chloride is dissolved in 20 mL of deionized water, and 8 g of porous cellulose particles are added. The mixture is stirred and impregnated at room temperature for 6 h to allow the lithium chloride to fully penetrate the porous cellulose particles. The resulting mixture is then dried at 60 °C to constant weight to obtain lithium chloride-supported porous cellulose particles, wherein the lithium chloride loading is approximately 50% of the carrier mass. The obtained lithium chloride-supported porous cellulose particles are added to the gel precursor solution of Example 6, and after dispersion, polymerization, and post-treatment, a self-regenerating high thermal conductivity and hygroscopic composite gel with a confined and immobilized carrier is obtained.
[0132] Example 8
[0133] Similar to Example 6, except that lithium chloride was prepared as the microcapsule core, and a polyurea or siloxane was used to form the coating layer to obtain hygroscopic salt microcapsules. These microcapsules were dispersed in a gel precursor solution and co-polymerized with a thermally conductive filler to form a composite gel. Specifically, 8 g of lithium chloride was dissolved in 10 mL of deionized water as the aqueous phase core; cyclohexane containing an emulsifier was used as the oil phase, and the aqueous phase was added dropwise to the oil phase under high-speed stirring to form a water-in-oil emulsion; subsequently, tetraethyl orthosilicate and ammonia were added, causing a hydrolysis-condensation reaction at the water-oil interface to form a siloxane coating layer. After the reaction was completed, the microcapsules were obtained by centrifugation, washing, and drying. The obtained lithium chloride microcapsules were dispersed in the gel precursor solution of Example 6 and co-polymerized with hexagonal boron nitride to obtain a self-regenerating, highly thermally conductive, and hygroscopic composite gel with microcapsule encapsulation and immobilization.
[0134] Comparative Example 1
[0135] Same as Example 1, except that the addition of hexagonal boron nitride and lithium chloride is omitted, while the other steps remain unchanged.
[0136] Comparative Example 2
[0137] Same as Example 1, except that 6g of hexagonal boron nitride modified with a silane coupling agent was added, but no shearing or orientation treatment was performed; it was simply dispersed by stirring. All other conditions were the same, specifically:
[0138] 1) Preparation of gel precursor solution
[0139] Add 10g acrylamide and 1.5g acrylic acid to 88g deionized water, stir to dissolve, then add 0.08g MBAA as a crosslinking agent and 0.10g APS as an initiator to obtain the precursor solution.
[0140] 2) Construction of a through-type thermally enhanced structure
[0141] Take 6g of hexagonal boron nitride powder modified with silane coupling agent and add it to the prepared precursor solution. Mix and stir for 30min to obtain the precursor system.
[0142] 3) Introduction of stabilizing moisture-absorbing components
[0143] Dissolve 8g of lithium chloride in 20mL of water and add it to the precursor system. Utilize the carboxyl groups introduced by acrylic acid to form ion association with lithium chloride to improve the fixation degree of the hygroscopic salt in the gel, thus obtaining a mixed precursor solution.
[0144] 4) Polymerization into a gel
[0145] The above-mentioned mixed precursor liquid was injected into a mold and polymerized at 60°C for 3 hours to obtain a flexible composite gel sheet.
[0146] 5) Post-processing
[0147] The obtained flexible composite gel sheet was left to stand for equilibration for 24 hours, and the surface was wiped and the edges were trimmed to obtain a single-layer self-regenerating high thermal conductivity and moisture-absorbing composite gel with a thickness of 1 mm.
[0148] Comparative Example 3: Unimmobilized hygroscopic salt gel
[0149] Compared with Example 1, lithium chloride was introduced by impregnation after gel molding, without forming ion association or immobilization with the polymer backbone. The other conditions were the same. Specifically, a thermally conductive enhanced gel sheet without lithium chloride was first prepared according to the method of Example 1. Then, the obtained gel sheet was immersed in 20 mL of aqueous solution containing 8 g of lithium chloride and impregnated at room temperature for 12 h to allow lithium chloride to enter the gel network. After removal, the residual solution on the surface was wiped off to obtain an unimmobilized hygroscopic salt gel.
[0150] In this comparative example, lithium chloride mainly exists in the gel in a free diffusion state and is not immobilized by carboxyl association, carrier confinement or microcapsule encapsulation.
[0151] Performance testing
[0152] Figure 1 The graphs show the heat dissipation performance of the composite gels obtained in Examples 1, 2, 3, and 6, and Comparative Examples 1 and 2. It can be seen that in Example 1, after introducing a through-type thermally conductive enhancement structure and a stabilized hygroscopic component, the surface temperature of the heat source is significantly reduced, and the temperature rise rate is slowed down. This indicates that the composite gel can more effectively transfer heat from the heat source interface to the gel interior and evaporation surface. Compared with the randomly dispersed thermally conductive filler gel of Comparative Example 2, Example 1 shows a more significant temperature reduction effect, indicating that a directional or through-type thermally conductive structure is more conducive to constructing an effective heat transfer path than random filler dispersion. Example 1 exhibits better temperature control capabilities than Examples 2 and 3, indicating a better overall matching relationship between its thermally conductive filler, hygroscopic component, and gel network. The multilayer composite gel of Example 6 exhibits even better temperature control effects, indicating that the partitioned design of the thermally conductive layer, the heat storage buffer layer, and the hygroscopic evaporation layer can further enhance the synergistic effect of heat transfer, heat buffering, and evaporative heat dissipation.
[0153] Figure 2The graphs show the cyclic stability of the composite gels obtained in Examples 1, 4, 5, 7, and 8, and Comparative Example 3. It can be seen that the cyclic stability of Comparative Example 3 decreases significantly with increasing cycle number, indicating that the unimmobilized hygroscopic salt is prone to migration, leakage, or precipitation during cycling. Examples 1, 4, and 5 maintain high stability after multiple cycles, indicating that gel network association and component regulation help improve the stability of the hygroscopic salt. Examples 7 and 8 maintain relatively stable hygroscopic and heat dissipation capabilities after multiple cycles, indicating that both carrier confinement immobilization and microcapsule encapsulation immobilization can effectively inhibit the migration, leakage, and precipitation of the hygroscopic salt. Example 8 shows further improved cyclic stability due to the stronger physical barrier effect of the microcapsule shell on lithium chloride. These results demonstrate that the present invention, through the design of stabilized hygroscopic components, can improve the cyclic regeneration capacity and long-term thermal management reliability of the composite gel.
[0154] The results show that when the composite gel obtained in this invention is cut into sheets that match the size of the hot end of the flexible thermoelectric device, and then attached to its hot end surface through an interfacial adhesion layer, heat from the hot end is transferred to the interior and outer surface of the gel through the through-type thermally enhanced structure on the side of the gel closest to the heat source. The moisture in the gel evaporates, carrying away latent heat. During shutdown or low heat flux phases, the stabilizing hygroscopic component absorbs moisture from the environment to compensate for water loss through evaporation, achieving cyclic regeneration.
[0155] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A self-regenerating, highly thermally conductive, and moisture-absorbing composite gel for thermal management of flexible devices, characterized in that, The composite gel is a single-layer integral structure or a multi-layer composite structure; The self-regenerating high thermal conductivity and moisture-absorbing composite gel comprises a flexible polymer gel matrix, a through-type thermal conductivity enhancement structure, and a stabilized moisture-absorbing component. The flexible polymer gel matrix is formed by cross-linking polymerization of acrylamide monomers; The through-type thermally conductive reinforcement structure is formed by continuously arranging highly thermally conductive fillers along the thickness direction and / or planar direction inside the gel matrix; The stabilized hygroscopic component includes hygroscopic salts, which are fixed in the gel matrix by means of carrier encapsulation; The through-type thermally conductive reinforcement structure is formed by arranging sheet-like or fibrous high thermal conductivity fillers through external field induction or shearing to form a continuous heat transfer path; The high thermal conductivity filler is selected from one or at least two of hexagonal boron nitride, alumina, aluminum nitride, graphene, carbon nanotubes, graphite sheets, carbon fibers, and metal nanowires. The stabilized hygroscopic component is immobilized by at least one of the following methods: loaded into porous microparticles or microcapsules and then embedded in a gel; the hygroscopic salt is selected from one or at least two of lithium chloride, calcium chloride, magnesium chloride, lithium bromide, potassium acetate, and potassium formate; The multilayer composite structure includes at least a thermally conductive layer and a moisture-absorbing and evaporating layer. The thermally conductive layer contains a higher content of high thermal conductivity filler than the moisture-absorbing and evaporating layer, and the moisture-absorbing and evaporating layer contains a higher content of hygroscopic salts than the thermally conductive layer. The outer surface of the composite gel is also provided with a surface radiation regulation layer, which has a medium-high infrared emissivity and is used to enhance heat dissipation in conjunction with evaporative heat dissipation.
2. The self-regenerating high thermal conductivity and hygroscopic composite gel according to claim 1, characterized in that, In the single-layer integrated structure, the flexible polymer gel matrix, the through-type thermally conductive enhancement structure, and the stabilized moisture-absorbing component are uniformly composited in the same layer.
3. The self-regenerating high thermal conductivity and moisture-absorbing composite gel according to claim 1, characterized in that, In the multilayer composite structure, each layer contains a flexible polymer gel matrix, the thermally conductive layer contains a through-type thermally conductive enhancement structure, and the moisture-absorbing and evaporating layer contains a stabilized moisture-absorbing component.
4. The self-regenerating high thermal conductivity and hygroscopic composite gel according to claim 1, characterized in that, The multi-layer composite structure also includes a heat storage buffer layer located between the heat-conducting layer and the moisture-absorbing evaporation layer.
5. The self-regenerating high thermal conductivity and hygroscopic composite gel according to claim 1, characterized in that, The acrylamide monomer is selected from one or at least two of acrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide and methacrylamide; The flexible polymer gel matrix further contains a comonomer selected from one or at least two of acrylic acid, methacrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, N-vinylpyrrolidone and hydroxyethyl acrylate. The crosslinking agent used for crosslinking polymerization is selected from one or both of N,N'-methylenebisacrylamide and polyethylene glycol diacrylate.
6. A method for preparing the self-regenerating high thermal conductivity and hygroscopic composite gel according to any one of claims 1 to 5, characterized in that, When the self-regenerating high thermal conductivity and moisture-absorbing composite gel is a single-layer integral structure, the following steps are included: Prepare a precursor solution containing acrylamide monomers, crosslinking agents, and initiators; High thermal conductivity filler is dispersed in the precursor liquid and a through-type thermally enhanced structure is constructed by directional arrangement. Hygroscopic salts are introduced into the precursor solution in an immobilized manner; The polymerization reaction is initiated to solidify the precursor liquid into a gel in one step, resulting in a single-layer monolithic self-regenerating high thermal conductivity and moisture-absorbing composite gel. When the composite gel is a multilayer composite structure, the following steps are included: Precursor solutions for the thermally conductive layer, the thermal storage buffer layer, and the hygroscopic evaporation layer were prepared separately. The thermally conductive layer precursor solution contained a higher content of high thermal conductivity filler than the hygroscopic evaporation layer precursor solution, and the hygroscopic evaporation layer precursor solution contained a higher content of hygroscopic salts than the thermally conductive layer precursor solution. The heat-conducting layer precursor liquid is cast and prepolymerized to form the heat-conducting layer. A heat storage buffer layer precursor liquid is poured onto the thermally conductive layer, and a second polymerization step is carried out to form a heat storage buffer layer. A moisture-absorbing evaporation layer precursor liquid is poured onto the heat storage buffer layer and then polymerized to form a moisture-absorbing evaporation layer, resulting in a multi-layered composite structure of a self-regenerating high thermal conductivity and moisture-absorbing composite gel.
7. The method for preparing the self-regenerating high thermal conductivity and hygroscopic composite gel according to claim 6, characterized in that, When the self-regenerating high thermal conductivity and hygroscopic composite gel is a single-layer integral structure, the amount of each component in the precursor liquid is as follows by weight: 10 parts by weight of acrylamide monomer, 1.5 parts by weight of comonomer, 0.08 parts by weight of crosslinking agent, 0.10 parts by weight of initiator, 3-9 parts by weight of high thermal conductivity filler, and 4-12 parts by weight of hygroscopic salt. When the self-regenerating high thermal conductivity and moisture-absorbing composite gel has a multilayer composite structure, the amounts of each component in the thermally conductive layer precursor solution, by weight, are: 8-10 parts by weight of acrylamide monomers, 0.5-2 parts by weight of comonomers, 0.04-0.10 parts by weight of crosslinking agents, 0.05-0.12 parts by weight of initiators, 6-10 parts by weight of high thermal conductivity fillers, and 60-100 parts by weight of water; the amounts of each component in the heat storage buffer layer precursor solution, by weight, are: 8-10 parts by weight of acrylamide monomers, 0.5-2 parts by weight of comonomers, 0.04-0.10 parts by weight of crosslinking agents, 0.05-0.12 parts by weight of initiators, 6-10 parts by weight of high thermal conductivity fillers, and 60-100 parts by weight of water. The precursor liquid for the hygroscopic evaporation layer contains 0.5-2 parts by weight of acrylamide monomer, 0.04-0.10 parts by weight of crosslinking agent, 0.05-0.12 parts by weight of initiator, and 60-100 parts by weight of water; the amounts of each component in the precursor liquid for the hygroscopic evaporation layer are as follows (by weight): 8-10 parts by weight of acrylamide monomer, 0.5-2 parts by weight of comonomer, 0.04-0.10 parts by weight of crosslinking agent, 0.05-0.12 parts by weight of initiator, 2-8 parts by weight of hygroscopic salt, 2-10 parts by weight of porous carrier, and 60-100 parts by weight of water.
8. The application of the self-regenerating high thermal conductivity and moisture-absorbing composite gel according to any one of claims 1 to 5 in flexible electronic devices.
9. The application of the self-regenerating high thermal conductivity and hygroscopic composite gel according to claim 8 in flexible electronic devices, characterized in that, The flexible electronic devices include wearable devices.
10. The application of the self-regenerating high thermal conductivity and hygroscopic composite gel according to claim 8 in flexible electronic devices, characterized in that, The flexible electronic devices include flexible thermoelectric devices or skin-attached sensor thermal management devices.
Citation Information
Patent Citations
Heat-conducting hydrogel and preparation method thereof
CN114752170A
Moisture absorption type transparent hydrogel as well as preparation method and application thereof
CN119019610A
High-thermal-conductivity organic silicon resin and preparation process thereof
CN119192858A